2019 IEEE Conference on Games (CoG) 2019
DOI: 10.1109/cig.2019.8847944
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Agents for Ad-Hoc Cooperation in Hanabi

Abstract: In complex scenarios where a model of other actors is necessary to predict and interpret their actions, it is often desirable that the model works well with a wide variety of previously unknown actors. Hanabi is a card game that brings the problem of modeling other players to the forefront, but there is no agreement on how to best generate a pool of agents to use as partners in ad-hoc cooperation evaluation. This paper proposes Quality Diversity algorithms as a promising class of algorithms to generate populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 24 publications
(42 reference statements)
0
15
0
Order By: Relevance
“…Liang et al showed that agents who use conversational implications and choose behaviors that emphasize the information given to the turn, and agents who emphasize narrowing the card's potential, are perceived as "human" who tend to feel human (Liang et al, 2019). Canaan et al suggested using a simulation of the play between AI, that the diversity of the player could be correspondent, if 2 parameters of "risk aversion" and "degree of communication" were set appropriately (Canaan et al, 2019). This study verifies whether AI agents with different tendencies of "risk aversion" can be implemented and actually adapted to human diversity.…”
Section: Background Of Hanabi Study: a Unique Testbed For Analyzing Human Cooperationmentioning
confidence: 99%
See 1 more Smart Citation
“…Liang et al showed that agents who use conversational implications and choose behaviors that emphasize the information given to the turn, and agents who emphasize narrowing the card's potential, are perceived as "human" who tend to feel human (Liang et al, 2019). Canaan et al suggested using a simulation of the play between AI, that the diversity of the player could be correspondent, if 2 parameters of "risk aversion" and "degree of communication" were set appropriately (Canaan et al, 2019). This study verifies whether AI agents with different tendencies of "risk aversion" can be implemented and actually adapted to human diversity.…”
Section: Background Of Hanabi Study: a Unique Testbed For Analyzing Human Cooperationmentioning
confidence: 99%
“…The conventional deterministic strategy is the algorithm proposed by Osawa (Osawa, 2015), which acts with the following priorities. This method is also widely used as a reference in other Hanabi studies (Canaan et al, 2019). Each process is conducted according to Figure 2B.…”
Section: Implementation Of Base Algorithmmentioning
confidence: 99%
“…Next to improving the quality of an agent, we are interested in the optimization of diverse agents with unique play-styles. The Multi-dimensional Archive of Phenotypic Elites (MAP-Elites) [9]) is a quality-diversity algorithm that has recently been used to create a diverse set of game-playing agents [22] and game-play elements [23].…”
Section: Map-elitesmentioning
confidence: 99%
“…Lastly, there is recent work on ad-hoc team play in Hanabi, in which agents get evaluated against a pool of different teammates (Canaan et al 2019;Walton-Rivers et al 2017).…”
Section: Related Workmentioning
confidence: 99%